DEKLARASI BALFOUR, LAHIRNYA SEBUAH PRASANGKA 100 TAHUN: Mengenang Satu abad Deklarasi Balfour 1917-2017 - Yecki Bus (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2017)
The Balfour Declaration was the official declaration of the United Kingdom of the status of the Land of Palestine announced by Foreign Minister Lord Arthur James Balfour on November 2, 1917. This declaration contains the support of the British Empire to make the Land of Palestine a place of state formation for the Jews. The existence of the declaration sparked great controversy and great suspicion, especially for the Muslim world about the evil conspiracy of Jews and Christians destroying Islam. This paper will explore the roots of the prejudices of hostilities by making the Balfour Declaration a central point. Based on historical search, it can be seen the nuances of conspiracy-scented conspiracy in this declaration. Although for the United Kingdom the Declaration was an attempt to win the war, but the feeling of being cheated already provoked a perpetual outrage toward the West for Muslims in the Middle East. This event is used as ammunition to inflame feelings of resentment and anger in many media publications in many Muslim countries. So the attention and reconciliation of Islam-West by lifting the 1917 incident is felt necessary to reduce the endless anger.